The function and role of bifaces in the Late Middle Paleolithic of southwestern France: Examples from the Charente and Dordogne to the Basque Country - Brenet, Michel (2018)
While Late Middle Palaeolithic industries are characterized by a well-documented diversity of stone tool types and blank production methods, the latter of which can at times be exclusively represented in certain assemblages, the bifacial tool component sometimes portrays clear similarities in use and manufacture method. Beyond sharing both comparable volumetric structures and arrangement of active and or prehensile areas, the recurrence in several assemblages of specific groups of bifacial tools used mostly for butchery is particularly striking. Here, we address several techno-economic and cognitive aspects of biface production and use combined with a consideration of their context. Is the same degree of variability in function and manufacture method equally visible in the retouched tool component? What scales of mobility or technical use-lives do these different bifacial tools portray? Do certain highly elaborate flake tools also reflect equally complex behaviors? How to interpret the presence of carefully manufactured pieces in non-local raw materials alongside others made in local varieties that are hardly reduced but nevertheless equally functional? Finally, which components may have carried a symbolic value or shed light on technical abilities or functional objectives evident in the conception, elaboration, use, and ultimate fate of these bifacial pieces. Several recently analyzed assemblages with a relatively significant bifacial component from the Charente, Dordogne and the Pyr en ees-Atlantiques departements show certain similarities or important differences. In characterizing the coexistence of flake production and bifacial-shaping, we attempt to reveal to what extent and in which ways certain bifacial tools stand out. When combined with technological and cognitive considerations, this approach provides new insights on an important behavioral facet of Neanderthal groups who occupied the Aquitaine Basin after the Last Interglacial.